(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To compare sexual quality of life in patients undergoing transurethral resection of the prostate (TURP) and Holmium laser enucleation of the prostate (HoLEP). Subjects and methods: A retrospective comparative study was conducted on patients with benign prostatic hyperplasia treated at 19-8 Hospital, Ministry of Public Security. The TURP group included 122 patients (January 2024-December 2024), while the HoLEP group included 52 patients (January 2023 to January 2025). Outcome measures included IPSS, QoL, IIEF-5, IIEF-15, and MSHQ-EjD scores assessed preoperatively and postoperatively (3 months for TURP and 12 months for HoLEP). Statistical analysis was performed using SPSS with a significance level of p < 0.05. Results: Both procedures significantly improved lower urinary tract symptoms and quality of life (p < 0.05). The mean IPSS score decreased from 22.71 ± 3.98 to 7.35 ± 3.53 in the TURP group, with similar improvements observed in the HoLEP group. Erectile function showed no statistically significant changes in either group (TURP: 18.62 ± 4.44 vs. 17.23 ± 6.5; HoLEP: 18.6 vs. 17.0; p > 0.05). In contrast, ejaculatory function significantly declined. The MSHQ-EjD score decreased from 16.26 ± 2.03 to 10.21 ± 5.18 in the TURP group and from 16.2 to 10.8 in the HoLEP group (p < 0.05). The rate of retrograde ejaculation was substantially higher in the HoLEP group (90%) compared to the TURP group (approximately 12.3%). Conclusion: Both TURP and HoLEP are effective in improving lower urinary tract symptoms while preserving erectile function. However, HoLEP has a more pronounced negative impact on ejaculatory function compared to TURP. Comprehensive preoperative counseling regarding potential sexual dysfunction, particularly ejaculatory disorders, is essential to optimize treatment decisions and patient quality of life.